Relationship between Big Five personality traits and eating disorder symptoms among university students - 612114 Nur Syakirah Azlan, 1995- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Psikologi dengan Pembangunan Sumber Manusia) - Universiti Teknologi Malaysia, 2017